A Low Cost Negative Pressure Wound Therapy Based on Arduino - Fikri Fahriansyah Pramono; Sari Luthfiyah; Triana Rahmawati; Nur Hasanah Ahniar (Department of electromedical engineering, Health Polytechnic of Surabaya, Ministry of Health Indonesia, 2020)
Instant life patterns and eating patterns and inappropriate exercise schedules are thought to be one of the causes of the increasing number of diabetes mellitus. Complications that can be caused by this disease are in the form of excessive susceptibility to infection, so that it develops into diabetic ulcers and can lead to amputations in these parts of the body. The purpose of this study is to design a tool used to treat diabetic ulcers. The contribution of this study is that the system can help remove fluid from the wound with controlled suction pressure so that it can facilitate the healing process faster. This Negative Pressure Wound Therapy (NPWT) tool works based on negative pressure from the vacuum motor by utilizing MPXV4115VC6U and MPXV5050VC6T1 pressure sensors at a pressure limit of 0 to -350 mmHg. Using an Arduino microcontroller for data processing, it will then be displayed on the 2x16 LCD. The MPX4115VC6U sensor produces a pressure of -55.97 mmHg when setting -50 mmHg and the resulting output is 3.32 volts, while the MPXV5050VC6T1 sensor produces a pressure of 51.18 mmHg at a setting of 50 mmHg and the resulting output is 3.18 volts, from the above data it can be seen if the MPX5050VC6TI sensor has a smaller error given